2021
DOI: 10.1186/s12913-021-06172-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishing evidence-based decision-making mechanism in a health eco-system and its linkages with health service coverage in 25 high-priority districts of Uttar Pradesh, India

Abstract: Background Achievement of successful health outcomes depends on evidence-based programming and implementation of effective health interventions. Routine Health Management Information System is one of the most valuable data sets to support evidence-based programming, however, evidence on systemic use of routine monitoring data for problem-solving and improving health outcomes remain negligible. We attempt to understand the effects of systematic evidence-based review mechanism on improving health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The role of maternal education in maternal service utilization has been observed in many studies within Ethiopia and elsewhere. 11,39,40 The disparity of maternal service utilization by wealth index has also been wellestablished in other studies. 10,12 The negative effect of distance for SBA or maternal care at the health facility is visible in this study and others.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The role of maternal education in maternal service utilization has been observed in many studies within Ethiopia and elsewhere. 11,39,40 The disparity of maternal service utilization by wealth index has also been wellestablished in other studies. 10,12 The negative effect of distance for SBA or maternal care at the health facility is visible in this study and others.…”
Section: Discussionmentioning
confidence: 82%
“…10 This process can be done through the regular review of routine health data and conducting root cause analyses of issues when needed. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies used a questionnaire (33%), observation or document review (29%), or both (29%) to measure data use. The exception was a study that developed a decision tracking system which served as their data source for the number and types of decisions taken and actions planned and completed [ 51 ]. About a third of studies (33%) collected self-reported measures about data use from health facility and/or district-level staff, without verification through observations or document review.…”
Section: Resultsmentioning
confidence: 99%
“…Greater investments are required to achieve this vision and to improve the quality of these data; the expectation is that data use will help improve data availability and quality over time. 19 These investments will be important for the GOUP to achieve its long-term vision of developing an integrated information communication technology architecture to allow the flow of health data across different data portals into a central dashboard repository that visually presents key program monitoring data to support management and decision making at various levels in the health system (unpublished data).…”
Section: Reflections On Achievements Challenges and The Way Forwardmentioning
confidence: 99%